Strategi Pengembangan Sumber Daya Manusia di Desa Wisata Sugih Waras Ngancar Kabupaten Kediri - Diah Nurdiwaty; Hestin Sri Widiawati; Dian Kusumaningtyas (LPMP Imperium, 2022)
This community service is carried out in the tourist village of Sugihwaras, Ngancar, Kediri district. The activity carried out is the development of human resources so that this tourist village can be known by many tourists. The role of technology today is very large to help marketing a business. There is no need to bother installing billboards or distributing pamphlets, but it is enough to provide a special place with an attractive contemporary design to meet photos. When marketing has reached the expected target, it is also necessary how to manage finances. Implementation of activities in the form of knowledge sharing and training. The method used is lecture, practice and question and answer. The purpose of this community service is to help the community in managing the Sugihwaras tourism village, Ngancar district so that what is expected is achieved and is able to compete with other tourist villages. Community service activities are going well and the community is very enthusiastic about following them without any significant obstacles.